Static Kirchhoff Rods under the Action of External Forces: Integration via Runge-Kutta Method. (9th January 2014) - Xavier Jr., Ademir L.
Abstract : This paper shows how to apply a simple Runge-Kutta algorithm to get solutions of Kirchhoff equations for static filaments subjected to arbitrary external and static forces. This is done by suitably integrating at once Kirchhoff and filament reference system equations under appropriate initial boundary conditions. To show the application of the method, we display several numerical solutions for filaments including cases showing the effect of gravity.